Behavioral Insights for Tax Compliance - World Bank (World Bank, Washington, DC, 2019)
This brief provides evidence from World Bank field experiments that consider the social, psychological, and economic factors influencing taxpayer decision-making. Complementary studies from Costa Rica, Guatemala, Poland, Latvia, and Kosovo demonstrate how context-specific, behaviorally informed messaging can offer an immediate, low-cost solution to bureaucratic and technological barriers.